Becker's World of the Cell - Hardin, Jeff Bertoni, Gregory Kleinsmith, Lewis J (Benjamin Cummings, 2012)
This book is intended as a comprehensive introduction to cellular and molecular biology for students preparing for careers in biology, medicine and related fields. Its goal is to present essential principles, processes and methodology.